The urbanisation of the North-Western provinces of the Roman Empire : a juridical and functional approach to town life in Roman Gaul, Germania Inferior and Britain - Pellegrino, Frida, (Archaeopress Roman archaeology ;, 2020)
This study investigates the development of urbanism in the north-western provinces of the Roman empire. Key themes include continuity and discontinuity between pre-Roman and Roman 'urban' systems, relationships between juridical statuses and levels of monumentality, levels of connectivity and economic integration, and regional urban hierarchies.